Sonodynamic Therapy: Advances and Challenges in Clinical Translation. (19th October 2018) - Lafond, Maxime; Yoshizawa, Shin; Umemura, Shin‐ichiro
Abstract : Sonodynamic therapy (SDT) consists of the synergetic interaction between ultrasound and a chemical agent. In SDT, the cytotoxicity is triggered by ultrasonic stimuli, notably through cavitation. The unique features of SDT are relevant in the clinical context more than ever: the need for efficacy, accuracy, and safety while being noninvasive and preserving the patient's quality of life. However, despite the promising results of this technique, only a few clinical reports describe the use of SDT. The objective of this article is to provide an extensive overview of the clinical and preclinical research conducted in vivo on SDT, to identify the limitations, and to detail the developed strategies to overcome them.